2021
DOI: 10.1038/s41598-021-95079-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of the occurrence and activity of Ixodes ricinus ticks and the prevalence of tick-borne diseases in eastern Poland

Abstract: Ixodes ricinus is the most widely distributed tick species in Europe. Mainly deciduous and mixed forests, pastures, and urban parks are habitats preferred by this species. I. ricinus ticks are also one of the most important reservoirs and vectors of human and animal infectious diseases on the continent. Borrelia burgdorferi s.l. spirochetes causing Lyme borreliosis (LB) in humans and tick borne encephalitis virus (TBEV), which is a causative agent of tick-borne encephalitis (TBE), are pathogens with the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…These regions are characterized by a large proportion of forest cover [54][55][56]. Our earlier study conducted in eastern Poland showed a significant positive correlation between TBE and LB prevalence rates and the surface area of forests [42]. Regional differences in TBE prevalence have also been reported in the Czech Republic, Austria, and Slovakia [57][58][59].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These regions are characterized by a large proportion of forest cover [54][55][56]. Our earlier study conducted in eastern Poland showed a significant positive correlation between TBE and LB prevalence rates and the surface area of forests [42]. Regional differences in TBE prevalence have also been reported in the Czech Republic, Austria, and Slovakia [57][58][59].…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study show that TBE is an especially important and growing problem in the Baltic, Central European, and Scandinavian countries, as the incidence of this disease in the analyzed period reached as high as 24.3/100.00 inhabitants in Lithuania (Figure 1). In many European countries, TBE is the second-most common human tickborne disease after LB in terms of the number of diagnosed cases [39][40][41][42]. Microclimatic conditions are the main factors that support the activity of ticks and, in an indirect way, the transmission of tick-borne pathogens [43].…”
Section: Discussionmentioning
confidence: 99%
“…I. ricinus is widely distributed across Europe. Its existence has been recorded in countries such as the UK, Germany, Sweden, Ukraine, Russia, Italy, France, Spain, Romania, Belgium, Austria, Latvia, and Lithuania [ 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. It is also found in Greece and particularly in Northwestern Greece and Crete, according to the current ECDC map distribution for Europe in March 2021 [ 35 , 36 ].…”
Section: How Climate Affects Tick Phenology—the Example Of ...mentioning
confidence: 99%
“…There are only few data for the spatial prediction of future distribution areas of TBEV [ 17 ]. The majority of these studies are based on aggregated data using NUTS (Nomenclature of Territorial Units for Statistics) level 3 [ 18 ]. A recently published work from Germany generated a sub-district risk-map for TBE, exclusively for southern Germany, based on 567 probable self-reported places of infection (POI) and 41 confirmed places/foci of infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%